2023
DOI: 10.3390/life13020268
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Roles and Applications of Proteinaceous Elicitors from Pathogens in Plant Immunity

Abstract: In interactions between pathogens and plants, pathogens secrete many molecules that facilitate plant infection, and some of these compounds are recognized by plant pattern recognition receptors (PRRs), which induce immune responses. Molecules in both pathogens and plants that trigger immune responses in plants are termed elicitors. On the basis of their chemical content, elicitors can be classified into carbohydrates, lipopeptides, proteinaceous compounds and other types. Although many studies have focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 131 publications
(203 reference statements)
0
4
0
Order By: Relevance
“…Although plants have acquired an array of defensive mechanisms against viral, bacterial or fungal pathogens, microbe-mediated induced resistance in plants have been of great interest in recent years as a novel microbiological tool in disease and insect pest management. [30][31][32][33][34] In this in-vitro study, B. bassiana strains BB252, BB72 and ARSEF-2860 were evaluated against TYLCV and aphid M. persicae. In the first two bioassays, different concentrations of conidial and filtrate suspensions of BB252 and BB72 strains were evaluated for their effect on TYLCV disease severity index.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although plants have acquired an array of defensive mechanisms against viral, bacterial or fungal pathogens, microbe-mediated induced resistance in plants have been of great interest in recent years as a novel microbiological tool in disease and insect pest management. [30][31][32][33][34] In this in-vitro study, B. bassiana strains BB252, BB72 and ARSEF-2860 were evaluated against TYLCV and aphid M. persicae. In the first two bioassays, different concentrations of conidial and filtrate suspensions of BB252 and BB72 strains were evaluated for their effect on TYLCV disease severity index.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested the activation of plant defense genes via signals generated by elicitor-receptor interactions at plant cell plasma membranes resulting in defense reactions such as the biosynthesis of phytoalexins and phenolic compounds and the activation of plant defense-related enzymes. 34,46,47…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations